Does Dyadic Coping Predict Couples’ Postpartum Psychosocial Adjustment? A Dyadic Longitudinal Study - Alves, Stephanie; Fonseca, Ana; Canavarro, Maria Cristina; Pereira, Marco (Frontiers in Psychology, 2020)
The way couples jointly manage pregnancy-related demands may prevent both members from experiencing psychosocial maladjustment after childbirth. This study examined (a) changes in dyadic coping (DC) and indicators of psychosocial adjustment (depressive and anxiety symptoms and quality of life [QoL]) from the second trimester of pregnancy (T1) to six-weeks postpartum (T2), (b) the actor and partner effects of DC at T1 on couples’ adjustment at T2, and (c) whether changes in DC over time would be associated with changes in the adjustment of both women and their partners. This study adopted a prospective quantitative dyadic longitudinal design. A total of 303 couples from Portugal answered self-report questionnaires assessing DC, depressive and anxiety symptoms, and QoL at T1, of which 290 were contacted at T2 to complete the same measures (n=138 couples returned the questionnaires). Results showed that first-time fathers’ QoL and both first and experienced fathers’ stress communication decreased over time, as did common DC (i.e., the way couples cope together with stress) perceived by both partners. First-time mothers reported higher increases in negative DC. The more positive DC the women provided to men at T1, the higher the internalizing symptoms of women at T2; the more the women communicated stress at T1, the higher the internalizing symptoms of men at T2. Both partners’ common DC at T1 positively predicted their QoL at T2. The larger the decrease in common DC over time, the greater the increase in internalizing symptoms of couples and the greater the decrease in their QoL. These findings suggest that DC strategies should be considered into the psychosocial care of couples becoming parents, as a relevant coping resource that partners could use to help each other in situations of stress. More than (exclusively) encouraging the men’s role as support providers, couples should be encouraged to reserve time for one another, to discuss each other concerns, and seeking for solutions as a team. These strategies should be promoted before and fostered after, childbirth. Likewise, clinicians should be aware that partners might not feel equally comfortable with specific DC strategies, and then should be carefully addressed among couples.